2015
DOI: 10.1007/s10877-015-9681-z
|View full text |Cite
|
Sign up to set email alerts
|

Permanent upper trunk plexopathy after interscalene brachial plexus block

Abstract: Interscalene brachial plexus block (IBPB) has been widely used in shoulder surgical procedures. The incidence of postoperative neural injury has been estimated to be as high as 3 %. We report a long-term neurologic deficit after a nerve stimulator assisted brachial plexus block. A 55 year-old male, with right shoulder impingement syndrome was scheduled for elective surgery. The patient was given an oral dose of 10 mg of diazepam prior to the nerve stimulator assisted brachial plexus block. The patient immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…We next examined the neurophysiologic mechanisms that may underlie the quick onset of pain after L5 SNT (dissecting scissors cut). Recent microneurography studies in patients suggested that development of SA and ectopic discharge in a subpopulation of DRG neurons after nerve injury might underlie spontaneous pain 1,2 . By conducting highly sensitive ex vivo electrophysiology recordings of DRG neurons, we found that 14 nociceptive neurons (C neurons) out of 17 neurons recorded from uninjured L4 DRG in 17 rats developed SA within a few minutes after L5 SNT, and remained active for at least 30 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next examined the neurophysiologic mechanisms that may underlie the quick onset of pain after L5 SNT (dissecting scissors cut). Recent microneurography studies in patients suggested that development of SA and ectopic discharge in a subpopulation of DRG neurons after nerve injury might underlie spontaneous pain 1,2 . By conducting highly sensitive ex vivo electrophysiology recordings of DRG neurons, we found that 14 nociceptive neurons (C neurons) out of 17 neurons recorded from uninjured L4 DRG in 17 rats developed SA within a few minutes after L5 SNT, and remained active for at least 30 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Denervation from axotomy causes a loss of peripheral sensory inputs. Yet, pain can develop rapidly after nerve injury in patients 14 . Neuropathic pain-related manifestations, such as spontaneous pain and tactile and heat hypersensitivity, are also observed in animal models of nerve injury and may last for weeks.…”
Section: Introductionmentioning
confidence: 99%
“…A large amount and prolonged injection of bupivacaine resulted in myopathy in a clinical situation with ISBPB, and myotoxic effects should be a concern if ropivacaine is administered for long periods, though the concern is less than for bupivacaine [ 16 17 ]. Intraneural injection of local anesthetics during ISBPB may cause severe plexopathy and neurologic deficits [ 18 ]. In the current study, we did not encounter the problem of migration of the perineural catheter in any patients, but this could happen during the postoperative analgesic period [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of ultrasound visualisation has revolutionised regional anaesthesia (RA) due to the possibility of observing the end of the needle and visualising the spread of local anaesthetic (LA) on the monitor. Moreover, it allows one to reduce the dose of LA [1], shortens the time of the onset of RA [2], minimises the rate of failed blocks [3] and the occurrence of brachial plexopathy [4], as well as the frequency of other unwelcome adverse events, such as intravascular injections of cardio-or neurotoxic LA [5], and diaphragm paralysis [6,7] with respiratory disorder [8]. In the end, IPBP produces appropriate analgesia for the postoperative period compared with general anaesthesia, which improves patients' satisfaction [9,10].…”
mentioning
confidence: 99%